Twitter Buzz and Citations: Who’s Tweeting Matters for Plastic Surgery Literature - Cedar Slovacek, MD; Tracey Cook, MD; Acacia Sheppard, BA; Pablo Palacios, MD; James P. Bradley, MD; Kevin C. Chen, BA, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Plastic surgery and social media have become inextricably linked through patient procurement, practice growth, and academic exposure. Other surgical fields have demonstrated that tweeting is positively correlated with increased citations. This study aimed to elucidate the effect of Twitter on traditional bibliometrics in plastic surgery and parse out the kinds of tweets that are most correlated with citations. Methods:. Articles from May to October of 2018 from Plastic and Reconstructive Surgery and Aesthetic Surgery Journal were analyzed to determine the citation count, number and backgrounds of Twitter users tweeting about the article, and total tweets. Multiple linear regression was performed to correlate these variables to citation count. Results:. A total of 369 articles were analyzed. Plastic and Reconstructive Surgery had significantly more average tweets per article compared to Aesthetic Surgery Journal (21.8 versus 10.2, P < 0.001), Additionally, a number of tweets (r = 0.45, P < 0.001) and reaching more total followers (r = 0.48, P < 0.001) were both positively correlated with citations. Multiple linear regression demonstrated that tweets from self-identified scientists were positively correlated with citations (r = 0.99, P = 0.001). Tweets from science communicators had no correlation with citations (r = −0.012, P = 0.726). Tweets coming domestically from the country of the author were also associated with more citations (r = 0.164, P = 0.013). Conclusions:. Twitter activity, including the number of followers reached, for an article is positively correlated with citations. Interestingly, the kind of person tweeting affected the citations as well. Domestic tweets and those from scientists were associated with more citations. This implies that Twitter can be an effective form of academic dissemination, provided the “right” Twitter users are promoting the article.